2022
DOI: 10.5935/1984-0063.20210031
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the sleep habits in individual and team-sport athletes using the Athlete Sleep Behavior Questionnaire and the Pittsburgh Sleep Quality Index

Abstract: Objectives There is limited large-scale data on maladaptive sleep practices in elite adult athletes and their influence on sleep characteristics. This study aimed to identify differences in sleep behaviours between individual and team-sport athletes using two sleep questionnaires. Material and Methods 407 (237 male, 170 female) elite adult athletes across sixteen sports (9 individual-sports, 7 team-sports) completed the Athlete Sleep Behavior Questionnaire (ASBQ) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…These reports have emphasized the need for athletes to regulate their sleep periods to improve their quality since sleep is one of the main tools to achieve optimal recovery ( 49 ). Not addressing these factors led to an increase in daytime sleepiness ( 12 ) and a decrease in sports performance ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These reports have emphasized the need for athletes to regulate their sleep periods to improve their quality since sleep is one of the main tools to achieve optimal recovery ( 49 ). Not addressing these factors led to an increase in daytime sleepiness ( 12 ) and a decrease in sports performance ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Global scores for the PSQI > 5 are considered poor sleep quality. The use of the PSQI with athletes had been widely reported with good reliability and validity ( 30 , 31 ), even during the pandemic ( 15 ), as well as with the athlete population ( 12 , 32 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research 9 has suggested that while sleep may be poor across athlete populations, challenges and habits differ between individual and team-sport athletes. Indeed, previous research 5 10 has shown significant differences between total sleep time and sleep efficiency between team and individual sports athletes. Furthermore, within team-sport athletes, sleep challenges may differ depending on the athlete's level.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3] Despite the importance of sleep on performance, researchers have reported that poor sleep is common in team sport athletes in training and precompetition environments, resulting in sleep debt. 4,5 Daytime naps are a commonly used strategy in an attempt to recover from sleep debt present amongst team sport athletes. 6 Previously, naps have been defined as a period of sleep less than 50% of an individual's nocturnal sleep.…”
Section: Introductionmentioning
confidence: 99%